Migrant-focused inequity, distrust and an erosion of care within Sweden's healthcare and media discourses during COVID-19 - Strange, Michael; Askanius, Tina (Frontiers in Human Dynamics, 2023)
Despite initial suggestions that the Covid-19 pandemic affected everyone equally, it quickly became clear that some were much worse affected than others. Marginalisation -including poverty, substandard accommodation, precarious or no employment, reduced access to healthcare and other key public goods -was clearly correlated with higher rates of both contagion and fatality. For Sweden, Covid-19 inequality could be seen along clear racial and socio-economic lines, with some of the first high death rates seen amongst Somali communities, where individuals had contracted the virus through unsafe employment as taxi drivers transporting wealthier Swedes home from their winter holidays. At the same time, actors on the extra parliamentarian far-right in Sweden were quick to blame the country's relatively high per-capita fatality rate on persons born outside Sweden working in the healthcare and care home sector. Media frames affirming racial stereotypes grounded in cultural racism circulated across the ecosystem of alternative media in the country. In both healthcare and the media, we see growing forms of exclusion disproportionately affecting migrants. Such intertwined exclusions in Sweden, as the article argues, are a sign of a wider disintegration of Swedish society in which individuals lose trust in both the core institutions as well as across different parts of society. Drawing on Davina Cooper's understanding of the relationship between the state and other public institutions with individuals as based on 'touch', the article explores how exclusionary practices impact this relationship. Our key argument is that, whilst ostensibly such practices often most materially hurt minority groups (e.g., migrants), they are indicative of -and accelerate -a broader disintegration of society through undermining a logic of 'care' necessary to sustain social bonds.